THE INFLUENCE OF PERSONAL VALUE ON FAMILY BUSINESS PROFESSIONALISM (SME CASE STUDY IN BATAM) - Susanti Susanti; Didi Sundiman (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2020)
The purpose of this research is to analyze the personal influence on the professionalism of the family business with a case study in the city of Batam. This research method is a quantitative approach method with a total of 111 respondents of SMEs in Batam. In this study, respondents were selected by filling out an online questionnaire. The criteria for selecting respondents are based on those who own a business or work in a family company. The results of this study were analyzed using the R version 4.0 program with the PLS-PM method. The test results show that three hypotheses are accepted, namely personal value has a significant effect on the variable decentralization, financial system and organization. Meanwhile, three hypotheses were rejected, namely personal values did not have a significant effect on the variable involvement of family members, human resource systems, and socio-cultural aspects.